DIFFERENTIAL EXPRESSION AND BIOINFORMATICS ANALYSIS OF MIR-184 IN PREGNANT AND NON-PREGNANT GOAT OVARIES - X. Zhang; J. Ding; Y. Ling; Y. Li; Y. Zhang; X. Zhang (Journal of Animal and Plant Sciences, 2013)
Ovarian follicular development and hormone secretion are complex and coordinated biological processes which alter during pregnancy. Ovarian function is tightly regulated by a multitude of genes, and may also be regulated by specific miRNAs. It is necessary to identify the differentially expressed miRNAs in the ovaries of pregnant and non-pregnant mammals, in order to fully understand the role of miRNA-mediated post-transcriptional regulation in mammalian reproduction. In an effort to uncover miR-184 importance in goats, we examined the differential expression pattern in the ovaries of 5 pregnant and 5 non-pregnant goats and gene ontology (GO) term enrichment of predicted target genes to determine the global biological functions of miR-184. Quantitative real-time PCR (q-PCR) analysis showed that miR-184 was expressed in the ovaries of pregnant goats, but was not expressed in the ovaries of non-pregnant goats. Moreover, thirty-eight target genes of miR-184 were predicted and 10 functional categories of GO terms were significantly overrepresented among the predicted miR-184 target genes. These categories can be broadly defined as regulation of development process and cellular biosynthetic process. Our results demonstrated that miR-184 was involved in various biological processes including pregnancy, developmental and cellular biosynthetic processes. Stephens and Moley 2009) . In the non-pregnant phase,
Keywords: miR-184 expression; GO term enrichment; ovaries; pregnant goat